(untitled) (African Journal of Biomedical Research, 2021)
Coronavirus, also known as COVID-19, is a new disease that has crippled almost every aspect of human activities today. Common symptoms of the virus include high fever (38oC and above), dry persistent cough, shortness of breath and sore throat. Recently, additional symptoms which include diarrhea, fever and headache have been reported in South Africa. Medicinal herbs have been in use since ancient times for the management of viral infections related to COVID-19. Nutrient deficiency has been observed in worst cases of COVID-19 infection. This review therefore explores the scientific-related literature on the use of garlic, ginger and lemon which are regarded as the healthiest of all natural herbs. They contain several natural vitamins (vit A, B1, B2, B3, B5, B6, C, E), minerals (potassium, magnesium, selenium, iron and zinc), and phenolic compounds (quercetin, gingerol, shogaol, paradol, limonene, limonins and hesperidin), omega-3s and -6s, allicin, ajoene and S-allylmercapto- L-cysteine. All these compounds are potent antiviral agents that can penetrate the mucous secretions of the respiratory system to strengthen the immune system and possibly prevent the replication of COVID-19. The combination of these natural herbs can block all the different pathways of COVID-19 infection and could provide instant relief to the early symptoms associated with the disease